(untitled) (CIPEEX, 2025)
The widespread training of the population in cardiopulmonary resuscitation (CPR) techniques is of fundamental importance to reduce deaths from cardiac arrest. However, the proper dissemination of high-quality CPR is still underperformed in Brazil. This study aims to compare the quality of CPR maneuvers across different periods of the medical course through the development of a data collection and analysis instrument. The study population consisted of 116 students from three different periods at UniEVANGÉLICA. This was a cross-sectional analytical study. Participants provided their anthropometric data, received instructions on proper CPR technique from the researchers, and then performed the maneuver on a CPR manikin equipped with a sensor for evaluation. The results showed that performance was below average across all periods studied, though the eighth period students performed CPR the best. Participant weight and gender had a significant influence, with heavier and male participants performing higher-quality CPR. It was concluded that improvements are necessary in CPR teaching during medical training, emphasizing especially the correct depth of compressions.